“Los anillos de la serpiente” (The snake rings) (Edison Cájas, 2020), audiovisual representation of the perpetrators and implicated subjects in a historical fiction short film - Sagredo Mazuela, Omar Luis (Revista de Historia Social y de las Mentalidades, 2023)
The article analyses the Chilean short film Los anillos de la serpiente (2020), a historical fiction film that depicts a civilian perpetrator in the early post-dictatorship years in Chile. From the so-called “turn to the perpetrator” in the field of historical me- mory studies, Lior Zylberman’s analytical principles are used to study the representation of perpetrators in film and Michael Rothberg’s theory of the “implicated subject” to ad- dress the complexity of civilian complicity. Based on this theoretical-methodological for- mulation, the central issues of this short film reviewed, with an emphasis on the modes of verbal and discursive figuration of the perpetrators, as well as the cinematic problema- tization of key historical issues, such as impunity and pacts of silence.